Pengaruh Konten Instagram @samsatsleman Terhadap Pemenuhan Kebutuhan Informasi Wajib Pajak di Kabupaten Sleman - Hafidh Awwalu Husna, Rezza; Chusumastuti, Dhety (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2025)
The increasing use of Instagram social media encourages Samsat Sleman to also distribute information to the public through Instagram content. The Instagram content of the @samsatsleman Instagram account can be a source of information to fulfill the information needs of the public about local tax services in Sleman Regency. The purpose of this study was to determine the effect of Instagram content on fulfilling the information needs of taxpayers in Sleman Regency. This study uses indicators of interest, expectations, satisfaction, and performance as well as the information needs approach. This research uses quantitative descriptive research methods.  The research population is followers of the @samsatsleman Instagram account and sampling using purposive sampling technique by paying attention to the respondent's criteria, namely as followers of the @samsatsleman Instagram account who have become taxpayers in Sleman Regency. The number of respondents in this study were 100 respondents. Data analysis in this study includes instrument tests, classical assumption tests, simple linear regression analysis, hypothesis testing and the coefficient of determination with the help of the SPSS 25 program. The results of the research that have been obtained show that the content of Instagram @samsatsleman has a positive and significant effect on fulfilling the information needs of taxpayers in Sleman Regency by 63.6% while the rest is influenced by other variables outside this study.